An analysis of sisters in islam’s (SIS) misinterpretation of the gender quality in the quran - Mohd Ghazali, Norzulaili; Mohd, Robiatul Adawiyah; Mohd Amin, Mohd Zohdi; Ahmad, Nadzrah (USIM, 2020)
The main agenda of feminism movements is to fight for gender equality between women and men. This agenda is advocated both by the Western as well as by some Muslim feminists. In Malaysia, a Muslim activist group who aggressively fight for gender equality is known as Sisters in Islam (SIS). This group has challenged and questioned the validity and reliability of the interpretation of some Quranic verses related to women, as it is felt that some of the verses were misinterpreted. To the group, the misinterpretation of the verses has led to misunderstanding regarding the positions and rights of women, which resulted into gender inequality. This paper aims to discuss the standpoint of SIS concerning gender equality by focusing on several issues; the superiority of men (qawwamah), the credibility of women as witness and the rights of women to be an imam. An analytical technique is used to analyse the SIS group’s viewpoint on the issues by referring several printed sources and articles published. These views will be compared with prominent Muslim scholars’ interpretation on related verses that has been used to find any contradiction or misinterpretation. The study concluded that SIS holds a misleading understanding on the interpretation of certain Quranic verses led by misrepresented claims on the unfounded contradiction between the verses of the Quran.